THU0627-HPR JOINT INVOLVEMENT SIGNIFICANTLY INFLUENCES QUALITY OF LIFE OF PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Natalucci, F.; Ceccarelli, F.; Cipriano, E.; Olivieri, G.; Perricone, C.; Spinelli, F. R.; Truglia, S.; Miranda, F.; Alessandri, C.; Conti, F.; Valesini, G.
Abstract : Background: Joint involvement is one of the most common features observed in Systemic Lupus Erythematosus (SLE), potentially involving up to 90% of patients [1]. Several patients' reported outcomes (PROs) have been employed to measure Quality of life (QoL) in SLE patients, but frequently not specifically developed for SLE patients. More recently, the LupusQoL has been validated, a disease specific questionnaire[2, 3]. Objectives: We focused at assessing the relationship between musculoskeletal manifestations and QoL in a large SLE cohort, by using the LupusQoL. Methods: SLE patients with a clinical history of joint involvement (arthralgia/arthritis – group A) were enrolled in the present study. SLE diagnosis was performed according to the revised 1997 ACR criteria. As a control group, we enrolled SLE patients without history of joint involvement (group B).Disease activity was assessed by the SLE Disease Activity Index-2000 (SLEDAI-2k). The activity of joint involvement was assessed by using the disease activity score on 28 joints (DAS28ESR ). The LupusQoL was administered to the enrolled patients (Group A and Group B). It consists of 34 items referring to eight domains: physical health (PH), pain (P), planning (PL), intimate relationships (IR), burden to others (BO), emotional health (EH), body image (BI) and fatigue (F). Results: Group A included 110 patients [M/F 8/102; median age 49 years (IQR 13), median disease duration 156 months (IQR 216)], while group B included 58 patients [M/F 11/47; median age 40 years (IQR 15), median disease duration 84 months (IQR 108)]. Group A showed a significantly lower disease duration and mean age in comparison with group B (P< 0.001 for both comparisons). As represented in figure 1, group A showed significantly lower values in all LupusQoL domains except for "burden to others" domain. Moreover, we observed an inverse correlation between DAS28ESR and all the LupusQoL domains in group A patients [PH (r=-0.5, P>0.0001), P (r=-0.5, P<0.0001), PL (r=-0.5, P<0.0001), IR (r=-0.2, P=0.006), BO (r=-0.4, P=0.0004), EH (r=-0.3, P=0.0009), BI (r=-0.4, P=0.001), F (r=-0.4, P<0.0001)]. Conversely, SLEDAI-2k values inversely correlated only with PL (r=-0.3, P=0.006), IR (r=-0.25, P=0.02), EH (r=-0.3, P=0.02). Conclusion: In the present study, by using a disease specific PRO, we found a poorer QoL in SLE patients with joint involvement in comparison with those without this manifestation. Moreover, DAS28ESR significantly correlated with all LupusQol domains, differently from SLEDAI-2k, suggesting the need to evaluate joint involvement with a specific activity index. References: [1]Cervera R et al. Medicine 1993 [2]McElhone K. et al. Arthritis Rheum 2007. [3]Conti F et al. Lupus 2014 Disclosure of Interests: Francesco Natalucci: None declared, Fulvia Ceccarelli: None declared, enrica cipriano: None declared, Giulio Olivieri: None declared, Carlo Perricone: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly, Simona Truglia: None declared, Francesca Miranda: None declared, cristiano alessandri Grant/research support from: Pfizer, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi, Guido Valesini: None declared